PERSEPSI WISATAWAN LOKAL TERHADAP CITRA KOTAGEDE SEBAGAI DESTINASI WISATA - Noviastuti, Nina; Februandari, Asmarani (Wahana Informasi Pariwisata : MEDIA WISATA, 2017)
Kotagede is one of heritage area in Yogyakarta that has many historical value and plays an important role for the existence of Yogyakarta nowadays. As a former capital of Mataram Islam Kingdom, this area has several historical and archeological sites, such as royal cemetery complex, the ruin of the fort, and other relics. Kotagede also has 170 heritage buildings that has been built around 1700’s until 1930’s. Kotagede also known from its silver industry. Based on Kotagede’s potentials, the government of Yogyakarta enacts this area as heritage area and becoming one of tourism destination in Yogyakarta. But the development of Kota Gede as tourism destination is still not optimal. Nowadays, Kotagede is more famous as silver industry area than as tourist destination. This research aims at determining destination image of Kotagede as tourism destination. This research use qualitative and quantitative method. The result showed the perception of local tourist on Kotagede’s destination image. Keywords: destination image, brand positioning, Kotagede